Effect of Ankle Dorsiflexors Facilitation on Gait in Cerebral Palsy - Supriya S. Jadhav1 , Mandar Malawade2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background- Cerebral palsy is a permanent and non-progressive group of disorders in the development of movement and posture causing functional and activity limitations. Children with cerebral palsy have dorsiflexor weakness and ankle deformity, which negatively affect their gait. This study mainly focuses on facilitation of dorsiflexors to improve gait. Facilitatory technigues are useful for facilitation and enhancement of muscle activity to achieve improved motor control. Objective: To find effect of ankle dorsiflexors facilitation on gait in cerebral palsy. Material and Methodology- In this pre-post interventional study 25 cerebral palsy children with gait abnormalities were included. Treatment protocol including facilitatory techniques was set for 6 weeks. After pre-post assessment data was analysed by using appropriate statistical techniques. Result- According to this study there is an improvement in gait parameters and ankle joint range of motion with P value <0.0001, which considered extremely significant. This indicates an overall improvement in gait of children with cerebral palsy. Conclusion- This study concludes that facilitation of dorsiflexors is beneficial for improving gait in cerebral palsy children.